1999
DOI: 10.1006/dbio.1998.9132
|View full text |Cite
|
Sign up to set email alerts
|

AP-2αTranscription Factor Is Required for Early Morphogenesis of the Lens Vesicle

Abstract: AP-2 transcription factors are a family of retinoic acid-responsive genes, which are involved in complex morphogenetic processes. In the current study, we determine the requirement for AP-2alpha in early morphogenesis of the eye by examining the nature of the ocular defects in AP-2alpha null and chimeric mice. AP-2alpha null embryos exhibited ocular phenotypes ranging from a complete lack of eyes (anophthalmia) to defects in the developing lens involving a persistent adhesion of the lens to the overlying surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
155
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(163 citation statements)
references
References 48 publications
8
155
0
Order By: Relevance
“…Inactivation of Raldh2, expressed in the optic vesicle between E8.5 and E9.5, disrupted optic cup and lens vesicle formation (Mic et al, 2004) and corneal-lenticular stalks are found in RXRα -/-; RARγ -/-compound mice (Kastner et al, 1994). Interestingly, the activity of a retinoic acid activated reporter construct is reduced in the lens placode of the Pax6 -/-mouse (Enwright and Grainger, 2000) and one of the possible targets of retinoic acid signaling in lens is the transcription factor AP-2α (West-Mays et al, 1999).…”
Section: Proliferation and Movement Of Lens Progenitor Cellsmentioning
confidence: 99%
“…Inactivation of Raldh2, expressed in the optic vesicle between E8.5 and E9.5, disrupted optic cup and lens vesicle formation (Mic et al, 2004) and corneal-lenticular stalks are found in RXRα -/-; RARγ -/-compound mice (Kastner et al, 1994). Interestingly, the activity of a retinoic acid activated reporter construct is reduced in the lens placode of the Pax6 -/-mouse (Enwright and Grainger, 2000) and one of the possible targets of retinoic acid signaling in lens is the transcription factor AP-2α (West-Mays et al, 1999).…”
Section: Proliferation and Movement Of Lens Progenitor Cellsmentioning
confidence: 99%
“…AP-2␣ knockout mice die perinatally and exhibit severe defects in cranial and body wall closure and skeletal structures (Schorle et al, 1996;Zhang et al, 1996;West-Mays et al, 1999). The ocular defects in these mice are so severe and appear so early, that it has not been possible to evaluate the function of AP-2␣ in retinal development.…”
Section: Introductionmentioning
confidence: 99%
“…The AP2 factors are developmentally regulated, retinoic acid-inducible genes that orchestrate a variety of cell processes including apoptosis, cell growth and tissue differentiation during embryogenesis (Zhang et al, 1996;Moser et al, 1997). Studies in mice have indicated an important role of AP2 factors in the development of neural crest, epidermal, placental and urogenital tissues (Zhang et al, 1996;Moser et al, 1997;Nottoli et al, 1998;West-Mays et al, 1999;Hilger-Eversheim et al, 2000). Early in embryogenesis, AP2a null/null mice have failure of cranial neural-tube closure and defects in cranial ganglia development (Zhang et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Later in embryogenesis, the mice develop craniofacial defects and thoraco-abdominoschisis with deformed or absent skeletal bones. A variety of ocular phenotypes have also been described including anophthalmia or abnormal lens morphogenesis (Nottoli et al, 1998;West-Mays et al, 1999). The AP2b null/null mouse phenotype is associated with normal glomerular and tubular differentiation, but at the end of embryonic development, the mice develop massive apoptotic death of the collecting duct and distal tubular epithelia (Moser et al, 1997).…”
Section: Introductionmentioning
confidence: 99%